A Cyclic Pentamethinium Salt Induces Cancer Cell Cytotoxicity through Mitochondrial Disintegration and Metabolic Collapse - Krejcir, Radovan; Krcova, Lucie; Zatloukalova, Pavlina; Briza, Tomas; Coates, Philip J; Sterba, Martin; Muller, Petr; Kralova, Jarmila; Martasek, Pavel; Kral, Vladimir; Vojtesek, Borivoj (International journal of molecular sciences, 2019)
Cancer cells preferentially utilize glycolysis for ATP production even in aerobic conditions (the Warburg effect) and adapt mitochondrial processes to their specific needs. Recent studies indicate that altered mitochondrial activities in cancer represent an actionable target for therapy. We previously showed that salt 1-3C, a quinoxaline unit (with cytotoxic activity) incorporated into a meso-substituted pentamethinium salt (with mitochondrial selectivity and fluorescence properties), displayed potent cytotoxic effects in vitro and in vivo, without significant toxic effects to normal tissues. Here, we investigated the cytotoxic mechanism of salt 1-3C compared to its analogue, salt 1-8C, with an extended side carbon chain. Live cell imaging demonstrated that salt 1-3C, but not 1-8C, is rapidly incorporated into mitochondria, correlating with increased cytotoxicity of salt 1-3C. The accumulation in mitochondria led to their fragmentation and loss of function, accompanied by increased autophagy/mitophagy. Salt 1-3C preferentially activated AMP-activated kinase and inhibited mammalian target of rapamycin (mTOR) signaling pathways, sensors of cellular metabolism, but did not induce apoptosis. These data indicate that salt 1-3C cytotoxicity involves mitochondrial perturbation and disintegration, and such compounds are promising candidates for targeting mitochondria as a weak spot of cancer.
Keywords: cancer therapy; Carbocyanines; mitochondria; Mitochondria; protinádorové látky; Cell Line, Tumor; kinasy AMP aktivovaných proteinkinas; proteinkinasy; TOR serin-threoninkinasy; kvartérní amoniové sloučeniny; TOR Serine-Threonine Kinases; autophagy; Protein Kinases; Quaternary Ammonium Compounds; lidé; karbocyaniny; mitofagie; Humans; Mitophagy; glucose metabolism; Quinazolines; nádorové buněčné linie; chinazoliny; AMP-Activated Protein Kinase Kinases; mitochondrie; Antineoplastic Agents